2006
DOI: 10.1590/s0074-02762006000700002
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular characterization of Van A-type vancomycin-resistant Enterococcus faecalis in Northeast of Brazil

Abstract: The isolation of vancomycin resistant enterococci (VRE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…These percentages of resistance are significant, while lower or occasionally comparable to those previously reported for enterococci recovered from human sources in Brazil (Mondino et al 2003, d'Azevedo et al 2004 ) and other locations (Lopes et al 2003). The observation of concomitant resistance to chloramphenicol, erythromycin, and tetracycline confirms the frequent resistance to multiple antibiotics among enterococcal isolates from humans sources in Brazil (Mondino et al 2003, Vilela et al 2006. Although a large proportion of (Bersos et al 2004).…”
Section: Discussionsupporting
confidence: 75%
“…These percentages of resistance are significant, while lower or occasionally comparable to those previously reported for enterococci recovered from human sources in Brazil (Mondino et al 2003, d'Azevedo et al 2004 ) and other locations (Lopes et al 2003). The observation of concomitant resistance to chloramphenicol, erythromycin, and tetracycline confirms the frequent resistance to multiple antibiotics among enterococcal isolates from humans sources in Brazil (Mondino et al 2003, Vilela et al 2006. Although a large proportion of (Bersos et al 2004).…”
Section: Discussionsupporting
confidence: 75%
“…In previous studies, vanA plasmid of 70 kb was found in both species of VRE from hospitals of several states in Brazil, suggesting horizontal transfer, what differs from the results of this study. 25,35 Regarding the plasmid family content, we checked whether each species had different rep genes or not. This was the first report of rep-genes of VRE plasmids from Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…The enterococus suspicious colonies were confi rmed genetically using genus [15] and species [16] specifi c primers for the PCR. The Uniplex PCR was used for the detection of antibiotic resistance genes in resistance strains.…”
Section: Molecular Methodsmentioning
confidence: 99%